Optimalisasi Branding Dan Packaging Produk UMKM Untuk Peningkatan Daya Saing Di E-Commerce - Nana Suarna; Nisa Dienwati Nuris; Mohamad Ibnu Abas; Muhammad Alfian Nur Rahmat (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the economy but often face obstacles in increasing product value, especially within the e-commerce ecosystem. This Community Partnership Program aims to optimize branding and packaging for partner MSME products to be more competitive and attractive in the digital market. The implementation methods include analyzing the condition of the MSMEs, providing intensive training on effective branding strategies and attractive as well as functional packaging design, followed by implementation assistance on e-commerce platforms. The expected outcomes of this activity are an enhanced brand image, improved visual appeal of products, as well as increased selling value and expanded online market reach for the partner MSMEs.